2015
DOI: 10.17507/jltr.0701.20
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence and Tolerance of Ambiguity in Academic Iranian EFL Learners' Willingness to Communicate

Abstract: Abstract-The present study was set up to detect any possible relationship among learners' emotional intelligence (EI), tolerance of ambiguity, and willingness to communicate inside the classroom. For this purpose, 64 undergraduate EFL university students were chosen. The instruments utilized in this study were a) Bar-On Emotional Quotient Inventory (EQ-I) to measure learners' emotional intelligence, b) Second Language Tolerance of Ambiguity Scale (SLTAS) to identify participants' tolerance of ambiguity, and c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Nevertheless, the researchers' core point was emotional intelligence, which might have had an effect on ambiguity tolerance, but no significant relation was detected between emotional intelligence and ambiguity tolerance. Vahedi and Fatemi (2016) also detected the relation between emotional intelligence and ambiguity tolerance, but their results are not meaningful like Rastegar and Kermani's study.…”
Section: Literature Reviewmentioning
confidence: 63%
“…Nevertheless, the researchers' core point was emotional intelligence, which might have had an effect on ambiguity tolerance, but no significant relation was detected between emotional intelligence and ambiguity tolerance. Vahedi and Fatemi (2016) also detected the relation between emotional intelligence and ambiguity tolerance, but their results are not meaningful like Rastegar and Kermani's study.…”
Section: Literature Reviewmentioning
confidence: 63%
“…However, the idea that the competent speaker is also emotionally competent is, at best, only implicit in these. More recently, studies have focused on the connections between emotional intelligence and academic achievement in TEFL (Jahandar et al, 2012;Abdolrezapour, 2013;Fani, 2015;Vahedi and Fatemi, 2016).…”
Section: Emotional Competencementioning
confidence: 99%
“…2. Emotional skills: ability to channel those emotions through linguistic means in the TL; to relate and respond to others' emotions; to use a variety of strategies for interpersonal contact that take into account one's own emotions and those of others; to anticipate conflicts in which emotional factors intervene and deal effectively with them through language; to show willingness to communicate and to engage actively and enthusiastically in conversation; to be able to build positive relationships based on reassurance, bonding, empathy and respect; to be assertive, able to respond to criticism, to recognise one's own mistakes and express joy at the success of others (based on Goleman, 1996;Dewaele, 2010;Council of Europe, 2001;Nieto Moreno de Diezmas, 2012;Vahedi and Fatemi, 2016;Martínez Agudo, 2018).…”
Section: Emotional Competencementioning
confidence: 99%
“…Studies that investigated TOALL in the context of reading found that high‐TOALL students showed higher reading comprehension (Kamran & Maftoon, 2012), less reading anxiety (Genç, 2016), and self‐reported reading success (Erten & Zehir Topkaya, 2009). Other insights into TOALL and L2 learning included (a) no association with receptive lexical knowledge yet a positive correlation with self‐perceived vocabulary knowledge (Basöz, 2015), (b) a relationship with willingness to communicate (Vahedi and Fatemi, 2016), and (c) an association with students' gender (Erten & Zehir Topkaya, 2009; Marzban, Barati & Moinzadeh, 2012), which other studies (Basöz, 2015; Sadeghi & Soleimani, 2016) could not corroborate, though.…”
Section: Learner Background In Sla Researchmentioning
confidence: 99%